Ensaio sobre roteiro documental: análise de três filmes contemporâneos sergipanos (2013–2016) - Batista, Marcus Vinicius Leite (2020)
This dissertation aims to bring and practices about the creation of the documentary script. We will follow a theoretical path presented by Luiz Rezende, using the concept of virtualization and, based on this analysis, we propose to proceed on the praxis of the documentary script with the help of readings by Sérgio Puccini. This dissertation was divided into three stages, to discuss the creation of the documentary script: a first stage, historical-theoretical-documentary, found in the first two chapters; the second stage, more about the script's praxis; and the third stage, applying taxonomies and approach methods to selected Sergipe documentaries. The purpose of this study is to expand investigations on the way of making and thinking about the documentary, delimiting this cut with contemporary films from Sergipe, due to the bias of its script.